Răspuns:
a) (x + 7)(x - 7) = x² - 7² = x² - 49
b) (3 - x)(3+x) = x² - 3² = x² - 9
c) (2x + 1)(2x - 1) = (2x)² - 1² = 4x² - 1
d) (3x + 2)(3x - 2) = (3x)² - 2² = 9x² - 4
e) (3a - b)(3a + b) = (3a)² - b² = 9a² - b²
f) (2x + 3y)(2x - 3y) = (2x)² - (3y)² = 4x² - 9y²
g) (x + 5y)(x - 5y) = x² - (5y)² = x² - 25y²
h) (3x - 4)(3x + 4) = (3x)² - 4² = 9x² - 16
i) (a - 6)(a + 6) = a² - 6² = a² - 36
j) (3x + 7)(3x - 7) = (3x)² - 7² = 9x² - 49
k) (5x + 4)(5x - 4) = (5x)² - 4² = 25x² - 16
1) (7x+3)(7x-3) = (7x)² - 3² = 49x² - 9